The Effect of Problem-Based Learning Model on Students’ Learning Outcomes Viewed from Learning Styles - Arni, Kurnia Julianti; Kosim, Kosim; Verawati, Ni Nyoman Sri Putu (Universitas Pendidikan Mandalika, 2024)
This study explores the effectiveness of the Problem-Based Learning (PBL) model on students' learning outcomes, focusing on how different learning styles—visual, auditory, and kinesthetic—affect its efficacy. Conducted at SMA Negeri 1 Narmada, the research employed a quasi-experimental design with a pretest-posttest nonequivalent control group setup to measure the impacts of PBL versus traditional teaching methods. Findings from the study revealed significant improvements in the physics learning outcomes for the experimental group, which engaged with the PBL model, compared to the control group that used conventional direct instruction methods. Statistical analysis using a two-way ANOVA showed a significant enhancement in learning outcomes associated with the PBL model (p = 0.030), but no significant interaction between learning styles and the learning model was found, indicating that the PBL model benefits all learning styles equally without preference. These results suggest that while PBL universally improves learning outcomes, individual learning styles do not significantly alter its effectiveness. The study highlights the potential of PBL to not only increase academic performance in physics but also to foster a more engaging and participatory learning environment. It underscores the importance of adopting educational models that accommodate diverse learning preferences and provide dynamic, student-centered learning experiences. This research contributes to the understanding of instructional effectiveness and supports the broader implementation of PBL in physics education to cater to varied educational needs and learning styles.